PENGARUH KOMITMEN ORGANISASI, BUDAYA ORGANISASI, DAN KEPUASAN KERJA TERHADAP KINERJA PERSONEL BIRO SUMBER DAYA MANUSIA (SDM) POLDA SULTRA - Samuddin Samuddin; Sudirman Zaid; Noval Nur (Pascasarjana Universitas Halu Oleo, 2023)
This study aims to: 1) determine the effect of organizational commitment, organizational culture and job satisfaction on the performance of the HR Bureau of the Regional Police of the Southeast Sulawesi, 2) determine the effect of organizational commitment on the performance of the personnel of the HR Bureau of the Regional Police of Southeast Sulawesi, 3) determine the influence of organizational culture on the performance of the personnel of the HR Bureau of the Regional Police. Southeast Sulawesi, and 4) knowing the effect of job satisfaction on the performance of the HR Bureau of the Regional Police of the Southeast Sulawesi Province.The object of this research is the HR Bureau of the Southeast Sulawesi Regional Police. The research population was 56 members of the police who served in the Southeast Sulawesi Regional Police HR Bureau and were used as research samples. The research data was collected using aquestionnaire, the research data was analyzed by Multiple Linear Regression using SPSS ver 22 to determine the results of the regression analysis of the influence of the independent variable on the dependent variable.The results of the study: 1) Together, organizational commitment, organizational culture and job satisfaction have a positive influence on personnel performance on members of the HR Bureau of the Regional Police of Southeast Sulawesi, 2) Organizational commitment has a positive and significant effect on personnel performance on members of the HR Bureau of the Regional Police of Southeast Sulawesi, 3) Organizational culture has a positive and significant effect on personnel performance at members of the Southeast Sulawesi Regional Police HR Bureau and 4) Job satisfaction has a positive and significant effect on personnel performance on members of the Southeast Sulawesi Regional Police HR Bureau.